Інструментарій та моделі оцінювання потенціалу економічного розвитку підприємств - Ємельянов, Олександр Юрійович (Національний університет "Львівська політехніка", 2019)
Метою цього дослідження є обґрунтування концептуальних, методологічних та методико-прикладних засад з розроблення і використання інструментарію та моделей оцінювання потенціалу економічного розвитку підприємств. Розроблено метод оцінювання потенціалу економічного розвитку підприємств на засадах встановлення та моделювання ієрархії властивостей підприємства, його окремих підсистем та елементів. Побудовано модель оцінювання потенціалу підвищення гнучкості та адаптованості підприємств до змін у зовнішньому середовищі. Розроблено інструментарій оцінювання потенціалу ресурсозберігаючих технологічних змін на підприємствах з урахуванням чинника ризику. Запропоновано показники оцінювання потенціалу технічного розвитку підприємств. Розроблено модель оцінювання потенціалу підвищення конкурентоспроможності підприємств. Розвинуто модель потенціалу підвищення фінансової стійкості підприємств. Целью этого исследования является обоснование концептуальных, методологических и методико-прикладных основ разработки и применения инструментария и моделей оценивания потенциала экономического развития предприятий. Разработан метод оценивания потенциала экономического развития предприятий на основе установления и моделирования иерархии свойств предприятия, его отдельных подсистем и элементов. Построена модель оценивания потенциала повышения гибкости предприятия и способности его к адаптации к изменениям во внешней среде. Разработан инструментарий оценивания потенциала ресурсосберегающих технологических изменений на предприятиях с учетом фактора риска. Предложены показатели оценивания потенциала технического развития предприятий. Разработана модель оценивания потенциала повышения конкурентоспособности предприятий. Развита модель оценивания потенциала повышения финансовой устойчивости предприятий. The purpose of this research is to substantiate conceptual, methodological, methodical and applied principles for the development and use of tools and models for assessing the potential of economic development of enterprises. A method of assessment of the potential of economic development of enterprises is developed in the work. This method is based on establishing and modeling the hierarchy of properties of the enterprise, its individual subsystems and elements, which involves defining chains of the corresponding properties and construction of their projections. It also allows to distinguish labile and conservative, managed and unmanaged properties of the enterprise and its constituents and to set such values of the managed properties, which provide the widest realization of the potential of economic development of enterprises. A model for assessing the potential of increasing the flexibility and adaptability of enterprises to changes in the external environment is proposed in the dissertation. According to this model, the potential for enhancing the flexibility and adaptability of enterprises can be determined by calculating the predicted growth in the proportion of potential losses from negative environmental impacts that the enterprise will avoid by improving its adaptation mechanisms. Tools for assessing the potential of resource-saving technological changes in enterprises is developed taking into account the risk factor. Tools involve the construction of many scenarios of the values of those indicators of the project implementation of resource-saving technological changes, which are characterized by the greatest unpredictability, the determining the maximum permissible amount of investment in the implementation of resource-saving technology and comparing this value with the actual need for investment in such implementation. The method of assessing factors of formation of potential of resource-saving economic development of enterprises is improved, which, in comparison with the existing methods, provides for setting limits of values of the index of efficiency of use of a certain resource of the enterprise and the index of physical volumes of sales of products, under which the growth of economic results of the enterprise is accompanied by a reduction in the consumption of a certain resource. Indicators for assessing the potential of technical development of enterprises, which, unlike the existing ones, are organized into four groups (generalizing, general, partial and basic), which form a certain hierarchy and exist in accordance with the management competencies of employees of enterprises in the field of management of their technical reequipment and resource support of economic activity. The assessment model of potential of increase of competitiveness of the enterprises is developed, which, unlike the existing ones, provides for determination of such parameters of quality of production and costs for its production and sale, at which the profit share of the enterprise is maximized in the total profit of all enterprises producing similar products. A model of assessing the potential for growth of the market value of enterprises is constructed. The use of this model, unlike similar models, allows determining the set of technical, technological and organizational-economic measures, as well as the optimal parameters of these measures, which provide the largest difference between the increase in the market value of enterprises and financial resources invested in achieving this growth. The conceptual approach to defining the concepts of “potential”, “enterprise potential” and “potential of development of the enterprise” was further developed. According to this approach, the potential of any object is equated with many of its external functional properties that the object exhibits or may exhibit in the particular state of the environment in which it is located. Accordingly, the potential of economic development of the enterprise is interpreted as the set of additional external functional properties that the enterprise may acquire under the particular state of the environment in which it is located, while increasing the value of its existing economic potential. Grouping of factors involved in forming the potential of economic development of economic entities by the following characteristics is realized: by location of relevant factors; by nature of influence on realization of potential of economic development of the enterprise; by the possibility of managing the relevant factors; by change (invariance) over a period of time; by the time necessary to change (activate) the relevant factors; by the characteristics of the relationships between the performance indicators of the enterprise; by place in the hierarchy; by the type of economic potential, which cause the relevant factors; by the method of evaluation factors; by the type of economic development of the enterprise; by the functional properties of the enterprise. Modeling of these factors is performed by constructing a pyramid of factors of formation of the potential of economic development of the enterprise, which contains six steps. The classification of barriers to realizing the potential of innovative development of enterprise is proposed. This classification involves the allocation of the following characteristics: the content of innovations, the method of their acquisition, the stage of the innovation process, the possibility and complexity of overcoming barriers, the objectivity and nature of the causes of the barriers. The average value of the various types of barriers to implementing a particular innovation (or set of innovations) in the sample of enterprises that have implemented or attempted to implement such an implementation is estimated in the dissertation by applying a multiplicative model of the actual level of innovation implementation. The model of potential of increase of financial stability of the enterprise by consistent execution of the following basic stages of calculations is developed: collecting the necessary information and assessing the existing level of financial stability of the enterprise; assessing the potential for growth in the amount of revenue that an entity can direct to repay its borrowings and pay interest on them; assessment of the potential of reducing the loan capital of the enterprise; assessing the potential of increasing the flexibility of the enterprise; forecasting the level of financial stability of the enterprise in case of full realization of the potential to increase this level; obtaining a quantitative assessment of the potential for improving the level of financial stability of the enterprise.
Инструментарий и модели оценивания потенциала экономического развития предприятий
Tools and models for assessing the potential of economic development of enterprises
Keywords: підприємство; потенціал; економічний розвиток; інструментарій; модель; властивість; гнучкість; конкурентоспроможність; фінансова стійкість; предприятие; потенциал; экономическое развитие; инструментарий; модель; свойство; гибкость; конкурентоспособность; финансовая устойчивость; enterprise; potential; economic development; tools; model; property; flexibility; competitiveness; financial stability; 330.34.01:330.341.1:658